Metabolic Control Status Related to Quality of Life in Children with Type 1 Diabetes Mellitus at Dr. M. Djamil General Hospital Padang - Ivanny Khosasih; Asrawati Nurdin; Eka Agustia Rini (HM Publisher, 2022)
Background. Type 1 Diabetes Mellitus (T1DM) is a chronic autoimmune disease requiring lifelong treatment. Good metabolic control could maintain an optimal quality of life. HbA1C is a reliable parameter of metabolic control. Poor metabolic control results in decreased quality of life for T1DM. This study aims to evaluate the relationship between metabolic control status and quality of life in children with T1DM at Dr. M. Djamil General Hospital Padang. Methods. This cross-sectional study on 52 T1DM children aged 8–16 years using consecutive sampling methods at the pediatric endocrinology outpatient clinic, Dr. M. Djamil General Hospital Padang, from April-September 2021. HbA1C was calculated using the High-Performance Liquid Chromatography (HPLC) method and classified into good and poor control. Quality of life was assessed using PedsQl 4.0 and classified as impaired and unimpaired. The Chi-square test was used for data analysis. The P-value of <0.05 was considered statistically significant. Results. The majority of respondents were girls (57.7%), and most of them had good nutritional status (73.1%). The mean age at diagnosis was 11.21±2.57 years, and they had suffered from T1DM for 2.21±1.28 years. A family history of diabetes was found in 57.7% of respondents. Complications found were hypoglycemia (19.2%) and diabetic ketoacidosis (50%). Poor metabolic control was found in 78.8% of respondents. Quality of life was impaired in 40.4% of respondents, especially in school functions. This study found that respondents with impaired quality of life had poor metabolic status (p<0.034). Conclusion. T1DM patients with poor metabolic control status have impaired quality of life.